Tension-induced toughening and conductivity enhancement in sequentially bridged MXene fibers. (1st October 2022) - Usman, Ken Aldren S; Zhang, Jizhen; Bacal, Christine Jurene O; Qin, Si; Mota-Santiago, Pablo; Lynch, Peter A; Naebe, Minoo; Henderson, Luke C; Hegh, Dylan; Razal, Joselito M
Abstract: Ti3 C2 T x MXene is a promising active material for developing fiber-based devices due to its exceptional electrical conductivity and electrochemical capacitance. However, fabricating robust fibers with high MXene content remains challenging due to shortcomings such as low interfacial adhesion between sheets and shrinkage-induced sheet disorientation during processing, leading to diminished physical and electrochemical properties. Here, we demonstrate the fabrication of tough, conductive, and electrochemically active fibers through a sequential bridging strategy involving calcium cation (Ca 2+ ) infiltration of cellulose nanocrystal (CNC)-bridged MXene, cross-linked and dried under tension. The resulting fibers exhibited a record toughness of ∼2.05 MJ m −3 and retained high volumetric capacitance (∼985 F cm −3 ), attributed to the synergistic CNC bridging, Ca 2+ cross-linking, and tension application during fiber drying. These fibers also surpass the conductivity of their unaligned pristine MXene counterpart (∼8347 S cm −1 vs ∼5078 S cm −1 ), ascribed to the tension-induced improvement in MXene alignment within these fibers, mitigating the undesirable effects of inserting an insulating CNC bridge. We anticipate that improving the toughness and conductivity of sequentially bridged MXene fibers will pave the way for the production of robust multifunctional MXene fibers, allowing their use in practical high-performance applications like wearable electronics and energy storage devices.